Building a model of navigational strategies for queer undergraduate students in STEM - Voigt, Matthew; Bolick, Margaret Ann; Cooper, Destinee; Otterbeck, Sarah; Smith, Abigail Rose; Wright, Chloe; Holloman, Clara (Frontiers in Sociology, 2023)
There is a critical need to foster inclusive educational spaces for Queer identifying students and to resist oppressive structures that seek to marginalize and inflict trauma on students because of their gender or sexual identity. Drawing on thematic analysis and Queer theory, we interviewed 11 Queer identifying STEM students to understand the navigational strategies they leveraged within higher education environments related to their Queer identity. We developed a cyclical model of navigational strategies employed by Queer STEM students that involved evaluating the environments, performing psychological identity calculations, and engaging in behavioral actions. Students evaluated the environment by attending to the diversity of gender representation, presence of other Queer individuals, and contextual factors conveyed based on disciplinary expectations. Students engaged in psychological identity calculations whereby they assessed beliefs about the relevance, importance, and fears related to their Queer identity, with few perceiving any benefits. Behavioral actions resulted in students building a chosen community, disclosing or shelving their queer identity, and advocating for representation. In order to support Queer students to thrive in educational contexts, researchers and practitioners should examine ways to increase representation, use inclusive pedagogical strategies, and understand the relevance of Queerness within disciplinary fields. Questioning the relevance or presence of Queerness in higher education environments only further serves to oppress, inflict trauma, and marginalize Queer students.